Pengembangan Media Bakiak Ular Tangga Untuk Meningkatkan Pemahaman Geometri Dasar Pada Anak Usia 5-6 Tahun - Fathimatuzzohrah Fathimatuzzohrah; Rabihatun Adawiyah; Zuhut Ramdani (UNIVERSITAS PGRI MADIUN, 2021)
This study aims to develop learning media of bakiak ular tangga to increase understanding of the basic geometry of children 5-6 ages. The development model of this study used Borg and Gall which consisted of 6 stages. Products developed were validated by a team of experts. The subjects of small scale were 5 children and large scale 25 children. The instrument used to collect the data was observation sheet. The results showed that the results of the validation of the media expert obtained a score of 31 with an average score of 3.8 which categorized